The Effectiveness of Diabetic Foot Gymnastics with Newspaper and Thorn Ball Media to Increase Foot Sensitivity in Type II Diabetes Mellitus Patients - Dewi Aini Zulfah; Mahalul Azam; Ari Yuniastuti (Universitas Negeri Semarang, 2026)
Diabetes Mellitus (DM) is a metabolic disorder in the body that occurs due to insulin function insufficiency resulting in high blood sugar levels. One of the complications of DM that is often experienced is neuropathy syndrome in the form of symptoms of peripheral nerve dysfunction which can affect foot sensitivity. Management of DM, namely physical activity in the form of leg exercises, can increase blood circulation, strengthen small muscles, thigh and calf muscles and reduce limitations in joint movement. The aim is to analyze the effectiveness of diabetes foot exercises using newspaper and thorn ball media to increase foot sensitivity in type II diabetes mellitus (DM) patients. Random Control Trial with pre post design involving 48 respondents in 3 intervention groups. Statistical analysis using Wilcoxon test with a 5% confidence interval using newspaper media obtained mark p value 0.013 and thorn ball media with value p value 0,029. Mann Withney test Newspaper foot exercises with values p value 0.008 and thorn ball media with value p value 0.012 is less than 0.05. In conclusion is DM foot exercises using newspapers and thorn balls are effective in increasing the sensitivity of the feet of patients with Diabetes Mellitus.